PENGARUH LATIHAN QUICK LEAT TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA PEMAIN SEPAK BOLA DI SSB PEKANBARU CITY SOCCER SCHOOL - Khodri, Ahmad Khodri Ahmad; ', Slamet Slamet; Wijayanti, Ni Putu Nita Wijayanti Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research want to know whether the effect of quick leat exercise toward the explosive power of leg muscle for football players in SSB Pekanbaru City Soccer School. The design of this research was an experimental research and the population was 24 people. The data of this research used purposive sampling or the samples determined by the researcher with the particular consideration. The samples were 16 people who often follow a competition as the main team. Instrument which done in this research was standing broad jump test. It aimed to measure the explosive power of leg muscle. After that, the data were statistically treated to examine the normality by using lilifors test in a significant standard 0.05α. The hypothesis was to know the effect of quick leat exercise toward the explosive power of leg muscle. Based on the analyses of T test stated that Tcountwas 3.092 and Ttablewas 1.753. It means that Tcount > Ttable. Based on analysis and statistics, the average of pree-test was 1.96 and the average of post-test was 2.26. It means that the data were normal. Therefore, there was the effect of quick leat exercise toward the explosive power of leg muscle for football players in SSB Pekanbaru City Soccer School.Keywords: Quick Leat, Explosive Power of leg muscle.